Shifts in Implementation of The Ngayah Tradition in Social Life of The Community in The Intaran Traditional Village, Sanur - Jayanti, Ni Wayan Desi Budha; Putri, Ni Putu Dinda Kalpika; Putri Chandra Sari, Anak Agung Ngurah; Anggreni, Ni Luh Putu Berlian; Wijayanti, Ni Komang Sri Rahayu (Fakultas Syariah dan Adab Universitas Nahdlatul Ulama Sunan Giri, 2024)
One of Bali's local wisdom that attracts tourists to visit Indonesia is the Ngayah Tradition, which has very important values in it. However, as time progressed, this tradition experienced a shift in people's social life. This research aims to determine and analyze the shift in the implementation of the ngayah tradition in the social life of the community in the Intaran Traditional Village, Sanur. The research method used is descriptive qualitative. There were twenty one research informants. The data obtained came from interviews, observations and documentation studies. Data analysis consists of three activity streams that occur simultaneously, namely: data reduction, data presentation, and drawing conclusions/verification. The results of the research show that a shift in the ngayah tradition is indeed occurring in society, especially in social life. In the past, the ngayah tradition that was carried out was thicker and more standard because the people's occupation at that time was only as farmers and fishermen. Meanwhile, nowadays, people's jobs are more diverse, so there has been a shift in the implementation of the ngayah tradition.